ANALISIS MANAJEMEN RESIKO K3RS DI INSTALASI GAWAT DARURAT RSUP Dr. M. DJAMIL PADANG - Gustina Indriati; Pandu Setiawan (Ensiklopedia of Journal, 2021)
Work accidents in the hospital can have 1.5 times bigger risk than other work. The hospital is a complex workplace, not only serving health but also a means of medical education and research facilities.General Hospital M. Djamil with accreditation A has implemented the work safety risk management system properly but not maximal yet. Based on that reasons, thisresearch was conducted to seethe risk management of work safety. This research was qualitative descriptive method with instrumentation used as data collection was direct interviews at Intensive Care Unit, from September to November 2020. The object of the study was the variable that became the focus of study Risk Management Analysis K3RS at RSUP M. Djamil Padang in 2020. This research found that there were 5 types of risk or danger in the ICUdepartementof RSUP Dr. M. Djamil Padang.These dangers were physical, chemical, biological, ergonomic, and psychological danger. There were 6 danger categories in high level and 4 danger categories in medium level, that were: the risk of contracting rabies while caring for patients,the risk of work fatigue and work stress. There were two risk control measures; administrative control and the use of personal protective equipment (PPE).